Anti‐PD‐L1 treatment enhances antitumor effect of everolimus in a mouse model of renal cell carcinoma. Issue 12 (13th December 2016) - Hirayama, Yukiyoshi; Gi, Min; Yamano, Shotaro; Tachibana, Hirokazu; Okuno, Takahiro; Tamada, Satoshi; Nakatani, Tatsuya; Wanibuchi, Hideki
Abstract : Immunotherapy based on blockade of the programmed death‐1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) axis has shown promising clinical activity for renal cell carcinoma (RCC) patients; however, the most effective use of these agents in combination with conventional targeted therapy remains to be resolved. Here we evaluated the therapeutic efficacy of the combination of the mTOR inhibitor everolimus (EVE) and anti‐PD‐L1 using an immunocompetent mouse model of RCC. We first assessed the in vitro effect of EVE on PD‐L1 expression in the human 786‐O and mouse RENCA RCC cell lines and found that EVE upregulated PD‐L1 expression in these RCC cell lines. We then treated RENCA tumor‐bearing mice with EVE and found that PD‐L1 expression was also increased in tumor cells after EVE treatment. To determine the antitumor effects of EVE alone, anti‐PD‐L1 alone, and EVE in combination with anti‐PD‐L1, we evaluated their antitumor effects on RENCA tumor‐bearing mice. A significant decrease in the tumor burden was observed in the EVE alone but not in the anti‐PD‐L1 alone treatment group compared with the control group. Importantly, the combination of EVE with anti‐PD‐L1 significantly reduced tumor burden compared with the EVE alone treatment, increasing tumor infiltrating lymphocytes (TILs) and the ratio of cytotoxic CD8 + T cells to TILs. The results of the present study demonstrated that anti‐PD‐L1 treatment enhanced the antitumor effect of EVE in a mouse model, supporting a direct translation of this combination strategy to the clinic for the treatment of RCC. Abstract : In this study, we assessed the therapeutic efficacy of the combination of the mTOR inhibitor everolimus (EVE) and anti‐PD‐L1 antibodies using an immunocompetent mouse model of renal cell carcinoma. We also evaluated the correlation between PD‐L1 expression and EVE treatment. Our findings demonstrated that while EVE increased PD‐L1 expression in tumor cells in vivo, a combination of EVE and anti‐PD‐L1 antibody treatment increased tumor‐infiltrating CD8 + T cells and resulted in tumor regression.